Cercetări pentru stabilirea influenţei materialului vegetal asupra preciziei determinării ionilor minerali din precipitaţii [Research on the effects of litter-fall and other vegetal materials on the precision of rain sample analysis] - Barbu I (Bucovina Forestieră, 1999)
Research made in the atmospheric deposition monitoring program have shown a great variability in the mineral ion content of rainwater samples, especially in samples took under the stand canopy. To prove that the litter in the samplers can influence the results of analysis of samples, it was organised a bifactorial experiment (contact time and the nature of litter) with each factor repeated 3-6 times. In distillate water were placed different amounts of litter, with the contact time of 3 to 30 days, after which were analysed with conventional methods. The obtained results led to following conclusions: (1) in small quantities of litter, the influence of litter on results of analysis was insignificant, (2) in high concentration of litter (1-2 g/l) the errors were of 20-30 % in K and N-NH 4 concentrations, while in the concentrations other ions the error was 5- 20 % from the annual mean concentration and (3) in very large quantities of litter (>5 g/l) the sample concentration can increase with values of 20-80 % from the annual mean concentration. The largest values can be encountered in K and N-NH 4 and the minimum values in Na